RP-HPLC method for quantitative estimation of naftifine hydrochloride in formulated products: development and validation - Shinde, Kajal Sunil; Jangme, Chandraprabhu Motichand; Patil , Abhinandan Raosaheb (Creative Pharma Assent, 2025)
Background: Naftifine hydrochloride is an allylamine antifungal agent commonly used to treat dermatophyte infections. It inhibits squalene epoxidase, a key enzyme in ergosterol biosynthesis, thereby disrupting the integrity of the fungal cell membrane. It exhibits broad-spectrum activity against dermatophytes, yeasts, and molds, and is typically formulated as a 1% topical cream or gel. Methodology: A rapid and robust reverse-phase high-performance liquid chromatography (RP-HPLC) method was developed and validated for the estimation of naftifine hydrochloride in a topical cream formulation (2% Naftifast, Zydus), in accordance with ICH and FDA guidelines. Chromatographic separation was achieved on an Inertsil ODS column using an isocratic mobile phase consisting of 35% acetonitrile, 40% methanol, 25% water, and 0.8% triethylamine (pH adjusted to 5.5 with acetic acid) at a flow rate of 1.4 mL/min. Detection was performed at 265 nm. Results and Discussion: Naftifine hydrochloride showed a retention time of approximately 4.0 minutes with a total run time of 6.0 minutes. The method displayed excellent linearity over a concentration range of 20–120 µg/mL (R² > 0.999). Recovery studies indicated a mean recovery of 100.4%. Precision was confirmed by relative standard deviation (RSD) values of less than 2%, demonstrating the method’s reproducibility. Conclusion: The proposed RP-HPLC method is simple, precise, and time-efficient. It is suitable for routine quality control of naftifine hydrochloride in pharmaceutical dosage forms due to its short analysis time and strong validation performance.